Boron Nitride Aerogels with Super‐Flexibility Ranging from Liquid Nitrogen Temperature to 1000 °C. (25th March 2019) - Li, Guangyong; Zhu, Mengya; Gong, Wenbin; Du, Ran; Eychmüller, Alexander; Li, Taotao; Lv, Weibang; Zhang, Xuetong
Abstract: Aerogels with extraordinary mechanical properties attract a lot of interest for their wide spread applications. However, the required flexibility is yet to be satisfied, especially under extreme conditions. Herein, a boron nitride nanoribbon aerogel with excellent temperature‐invariant super‐flexibility is developed by high temperature amination of a melamine diborate precursor formed by hydrogen bonding assembly. The unique structure of the aerogel provides it with outstanding compressing/bending/twisting elasticity, cutting resistance, and recoverable properties. Furthermore, the excellent mechanical super‐flexibility is maintained over a wide temperature range, from liquid nitrogen temperature (−196 °C) to higher than 1000 °C, which extends their possible applications to harsh environments. Abstract : Super‐flexible boron nitride nanoribbon aerogels are produced by high temperature amination of melamine and boric acid assemblies, showing outstanding compressing/bending/twisting elasticity, cutting resistance, and recoverable properties over a wide range, from liquid nitrogen temperature to more than 1000 °C.